Call centres and the quality of work life: towards a research agenda - Hannif, Z.; Burgess, John; Connell, Julia (Sage Publications Ltd., 2008)
Concerns about job quality have become more widespread, crossing all industries and occupations. The call centre sector in particular has risen to the forefront of discussions about job quality because of the rapid growth and development of these new forms of work organization over the past two decades. However, despite there being an extensive quality of work life literature, and emerging research on call centre job quality, there is yet to be a study that systematically links the quality of work with employment in the call centre context. This article outlines current debates, highlighting the importance of bringing together and marrying these two branches of research. A qualitative research agenda constituting case study analysis of two call centres is introduced. A framework grounded in a job characteristics approach, comprising 10 key job-quality elements is also proposed as a means of examining the quality of work life in this context.